India's economy : some issues and answers - Acharya, Shankar N. (New Delhi : Academic Foundation, 2003)
On suggestions to policy makers on economic issues of India post 1997/98 based on experiences in past 50 years.
Includes bibliographical references.
Keywords: India -- Economic policy -- 1991-; India -- Economic conditions -- 1947-